(untitled) (European Journal of Pure and Applied Mathematics, 2023)
This research article demonstrates an efficient method for solving partial integro-differential equations. The intention of this research is to establish the solution of some different classes of integral equations, by utilizing the double Laplace ARA transform. We present some definitions and basic concepts related to the double Laplace ARA transform. The results of the examples support the theoretical results and show the accuracy and applicability of the presented approach.